A tool to improve code‐first Web services discoverability through text mining techniques. (28th April 2014) - Mateos, Cristian; Rodriguez, Juan Manuel; Zunino, Alejandro; Tse, T. H.; Gotlieb, Arnaud; Chen, Zhenyu
Summary Service‐oriented development is challenging mainly because Web service developers tend to disregard the importance of the exposed service APIs, which are specified using Web Service Description Language (WSDL) documents. Methodologically, WSDL documents can be either manually generated or inferred from service implementations using WSDL generation tools. The latter option, called code first, is the most used approach in the industry. However, it is known that there are some bad practices in service implementations or defects in WSDL generation tools that may cause WSDL documents to present WSDL anti‐patterns, which in turn compromise the chances of documents of being discovered and understood. In this paper, we present a software tool that assists developers in obtaining WSDL documents with as few WSDL anti‐patterns as possible. The tool combines text mining and meta‐programming techniques to process service implementations and is developed as an Eclipse plug‐in. An evaluation of the tool by using a data‐set of real service implementations in terms of anti‐pattern avoidance accuracy and discovery performance by using classical Information Retrieval metrics—Precision‐at‐n, Recall and Normalized Discounted Cumulative Gain—is also reported.Copyright © 2014 John Wiley & Sons, Ltd.